Oxford Handbooks Online 2011
DOI: 10.1093/oxfordhb/9780199734610.013.0041
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Approach to Studying Diversity in Organizations

Abstract: In this article, we distinguish between positive findings in diversity research and a positive approach to studying diversity. We first review and integrate research on diversity from organizational behavior, social psychology and sociology from 1998-2010 that has already documented positive findings in relation to diversity. We discuss this research using two broad categories: (1) to studying diversity and describe some examples of organizational scholarship that has taken such an approach. We also discuss s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…This study was conducted in the context of positive organisational behaviour and focused on the psychological capacities of the participants (Luthans, 2002a). In particular, the authors viewed gender as a selected diversity category in positive organisational psychology and the study, therefore, contributes to building the genderrelated positive organisational literature (Ramarajan & Thomas, 2010). It should help to fill the void of positive organisational behaviour and gender research highlighted by Sandelands (2002) and also aims to contribute to improvements in experiences of health and well-being in the organisation (Youssef & Luthans, 2007) by firstly researching the concepts of life orientation, health strategies, sense of coherence and gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was conducted in the context of positive organisational behaviour and focused on the psychological capacities of the participants (Luthans, 2002a). In particular, the authors viewed gender as a selected diversity category in positive organisational psychology and the study, therefore, contributes to building the genderrelated positive organisational literature (Ramarajan & Thomas, 2010). It should help to fill the void of positive organisational behaviour and gender research highlighted by Sandelands (2002) and also aims to contribute to improvements in experiences of health and well-being in the organisation (Youssef & Luthans, 2007) by firstly researching the concepts of life orientation, health strategies, sense of coherence and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that emphasising positive organisational behaviour impacts strongly on individual and group-related behaviours in organisations (Lyubomirsky, 2013;Mendes & Stander, 2011;Seligman, 2011). Since 2002, there has been an increase in research dealing with diversity issues and positive organisational behaviour, distinguishing between positive findings in diversity research and positive approaches to studying diversity (Ramarajan & Thomas, 2010). However, most of the research over the past five decades highlights the fact that: 'researchers may not believe that positive and diversity can be studied together' (Ramarajan & Thomas, 2010, p. 22).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no assertion that diversity is good or bad, there is a consensus that an organisational diversity climate is a ‘crucial contextual catalyst that brings out the benefits of diversity’ (Chen, Liu, and Portnoy, 2012, 94). A general suggestion from research on workplace diversity and diversity management is that employees and organisations benefit when an inclusive work environment is well established within the organisation (Adamovic, 2018, 2020; Ramarajan and Thomas, 2010). In other words, an organisation with a pro‐diversity climate often treats diversity as an asset and can foster the conditions that leverage its benefits or lessen its possible negative effects (Chen, Liu, and Portnoy, 2012; Shore et al., 2009).…”
Section: Theoretical Background: Diversity Climatementioning
confidence: 99%
“…Initially, we implemented the kaizen philosophy through meetings with a Vibe Tribe, a group of individuals tasked with encouraging "positive intergroup relations, " characterized by members of both minority and majority groups having positive experiences working with each other (Ramarajan and Thomas, 2012). The Vibe Tribe provided a platform that directly targeted areas of improvement, in accordance with the Kaizen Philosophy, focusing team culture, and accountability.…”
Section: Transformational Leadership and The Kaizen Philosophymentioning
confidence: 99%